1989
DOI: 10.1084/jem.170.3.751
|View full text |Cite
|
Sign up to set email alerts
|

The specificity of rejection and the absence of susceptibility of pancreatic islet beta cells to nonspecific immune destruction in mixed strain islets grafted beneath the renal capsule in the rat.

Abstract: The specificity of rejection of isolated pancreatic islets was examined in the rat using a quantitative model in which syngeneic (DA) or a mixture of syngeneic and allogeneic (DA and LEW or PVG) islets were implanted beneath the capsule of the kidney of nondiabetic normal rats (DA). 3 wk after transplantation total insulin extraction assays of the kidney with its islet implant together with immunohistological examination of the site of transplantation for evidence of syngeneic or allogeneic tissue demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 33 publications
(25 reference statements)
2
14
0
1
Order By: Relevance
“…Such bystander killing has been shown to be mediated by Fas/Fas ligand (CD95/CD95 ligand) interactions or by TNF (1) and was dependent on the allele of MHC expressed by the "bystander" cells in some settings (2) but not others (4). In transplant models, using a mixture of syngeneic and allogeneic or xenogeneic islets (5,6) or with allophenic skin grafts (7,8), results supported the concept of selective killing of specific target cells. In contrast, other skin transplant models have shown significant bystander damage to adjacent syngeneic cells (9), and bystander injury occurred in mixed xenogeneic and syngeneic islets in primed recipients (10).…”
mentioning
confidence: 79%
“…Such bystander killing has been shown to be mediated by Fas/Fas ligand (CD95/CD95 ligand) interactions or by TNF (1) and was dependent on the allele of MHC expressed by the "bystander" cells in some settings (2) but not others (4). In transplant models, using a mixture of syngeneic and allogeneic or xenogeneic islets (5,6) or with allophenic skin grafts (7,8), results supported the concept of selective killing of specific target cells. In contrast, other skin transplant models have shown significant bystander damage to adjacent syngeneic cells (9), and bystander injury occurred in mixed xenogeneic and syngeneic islets in primed recipients (10).…”
mentioning
confidence: 79%
“…62 There is evidence that allogeneic rejection of islets is contact-dependent because grafts consisting of mixed syngeneic and allogeneic islets resulted in the destruction of only the allogeneic islets. 63 It remains unclear how allografts are destroyed in vivo, but clearly perforin-independent mechanisms exist.…”
Section: Allogeneic Islet Graft Rejectionmentioning
confidence: 99%
“…This pattern suggests that allospecific cytotoxic cells rather than nonspecific effector mechanisms, such as the action of cytokines, destroy allogeneic patches. Consistent with this concept, Sutton et al (15), studying grafts consisting of admixed allogeneic and syngeneic islets of Langerhans, observed that the allogeneic islets were destroyed whereas syngeneic islets, even those adjacent to allogeneic islets, survived. However, neither of these seminal studies provides a fully satisfying answer.…”
Section: Jeffrey L Plattmentioning
confidence: 86%